KARAKTERISTIK KAPASITAS PERBANDINGAN MASSA MATEIAL TiO2:rGO PADA SUPERKAPASITOR - Marito Siagian, Sinta; Chrisna HS, Samaria; R Tampubolon, Ferdinan; Khiarani, Suci; Ginting, Agustina; Devita, Rischa (CV RIFAINSTITUT, 2023)
The aim of this research is to analyze the capacitance value of a supercapacitor using TiO2 and coconut shells as organic rGO from natural waste. The method used to produce this material is to use wet chemistry by adding H2SO4 to coconut shell carbon to improve its electrolyte properties. After that, when applying a supercapacitor, phosphoric acid is used. The results obtained from this research are that the highest value is in a ratio of 1:1 at a value of 489 µF with a decrease in the last measurement at a value of 426 µF, while the lowest capacitance value is in a ratio of 1:3. Based on the measurement results obtained a capacitance value of 58 µF and a reduction value capacity up to 53 µF.